Pengembangan Pekarangan Hijau sebagai Intervensi Sosial dalam Meningkatkan Kesejahteraan Keluarga - Mey Yulan Moko; Siti Rahmawaty Igirisa; Sulistia Harun (Fakultas Hukum Universitas Semarang, 2025)
The development of green home gardens is an important strategy for improving family welfare, particularly in Balayo Village, which has extensive yard potential that remains underutilized. The urgency of this community service program arises from the low level of public knowledge and skills in managing home gardens, as well as the need to strengthen household food security in accordance with Law No. 18 of 2012 on Food and the obligation to protect the environment as mandated by Law No. 32 of 2009 on Environmental Protection and Management. The program was implemented using the Participatory Assessment approach, which included problem identification, potential analysis, solution selection, community outreach, and technical assistance in preparing planting media, seedling cultivation, and garden management. The results indicate improved community knowledge, skills, and awareness regarding green home garden management; the formation of learning groups; and an increase in household green space, air quality, and food production. The program also strengthened social interaction and community participation in environmental conservation. Overall, the development of green home gardens proved to be an effective social intervention for enhancing food security, family welfare, and environmental quality at the household level. Keywords: green home garde; social intervention; family welfare; food security.